2006
DOI: 10.1021/bi061334p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Domains of Clostridium septicum Alpha Toxin

Abstract: Alpha toxin (AT) is the major virulence factor of Clostridium septicum that is a proteolytically activated pore-forming toxin belonging to the aerolysin-like family of toxins. AT is predicted to be a three-domain molecule based on functional and sequence similarity with aerolysin, for which the crystal structure has been solved. In the present study we have substituted the entire primary structure of AT with alanine or cysteine in order to identify those amino acids that comprise functional domains involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…In other pore-forming toxins mutations affecting toxin oligomerization correlated with a severe disruption in toxicity, suggesting that oligomerization is an essential step (21)(22)(23)(24)(25). To determine the role of oligomer formation for Cry1Ab toxin action, we isolated and characterized single point mutations that affected toxin oligomerization.…”
Section: Bacillus Thuringiensis (Bt)mentioning
confidence: 99%
“…In other pore-forming toxins mutations affecting toxin oligomerization correlated with a severe disruption in toxicity, suggesting that oligomerization is an essential step (21)(22)(23)(24)(25). To determine the role of oligomer formation for Cry1Ab toxin action, we isolated and characterized single point mutations that affected toxin oligomerization.…”
Section: Bacillus Thuringiensis (Bt)mentioning
confidence: 99%
“…Therefore, the folate receptor alpha is localized on the outer surface of the cell membrane and could serve as the membrane attachment site for extracellular proteins, possibly including HALT-1. This hypothesis is supported by the fact that the alpha-toxin of Clostridium septicum binds to the GPI-anchored form of folate receptor alpha (Gordon et al 1999) before it is cleaved approximately 4 kDa from the C-terminus to become an active cytolysin (Melton-Witt et al 2006). Similarly, we suggest that folate receptor alpha could serve as a membrane receptor for HALT-1 instead of the lipid sphingomyelin, which has been previously thought to be the solely attachment site for HALT-1 on the cell membrane (Liew et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The modified csa genes (30,31) were PCR amplified from expression vectors with the high-fidelity DNA polymerase Pwo (Roche) and primers JRP1075 (5Ј-ATCCCGCGAAATTAATAC-3Ј) and JRP1923 (5Ј-CGT TAATTAATATCAATTTTTTTATCA-3Ј), where JRP1923 incorporates a unique PacI site and the additional 3Ј adenosine native to JIR6086 and other C. septicum alpha-toxin sequences (4). The product was then cleaved with PacI and BbsI and cloned into csa suicide plasmid pJIR2230, which carries an erm(B) gene flanked by 5Ј and 3Ј csa fragments (26), so that the erm(B) gene was replaced with an internal csa fragment that included the required mutation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies (30,31) provided greater insights into the role of the three domains of alpha-toxin. Alanine scanning mutagenesis of the entire protein revealed that residues important in receptor binding were restricted to loops 1 and 3 and to an ␣-helix in domain 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation